Retinal Thickness Associates with Cognition Dysfunction in Young Adult with Type 1 Diabetes in Taiwan - Jung-Lung Hsu; Pei-Shin Gu; Eugene Yu-Chuan Kang; Chi-Chun Lai; Fu-Sung Lo (Journal of Diabetes Research)
Background. Several factors could affect the cognitive dysfunction in patients with type 1 diabetes (T1D). Objectives. To report the characteristic of cognitive dysfunction in T1D and find its association with the retinal thickness. Subjects. We recruited one hundred and seven patients with T1D in our study. Methods. Detailed clinical and demographic factors and Cambridge Automated Neuropsychological Test Battery (CANTAB) were performed in all participants. The age at onset>5 years old and ≤5 years old groups was defined as old- and young-onset groups. The levels of the average values of 5-year glycated hemoglobin (HbA1c_5) before study were collected. Ophthalmic study and central retinal thickness (CRT) were performed. Results. The median age of T1D was 24.9 years old and 57 participants were women. The median age at onset was 7.4 years old, and mean disease duration was 17.2 years. After adjusting off multiple covariates by the regression analyses, the young-onset group had significantly a longer latency in sustained attention than old-onset group (P=0.02). The HbA1c_5 showed a significantly negative association with the sustained attention (P=0.03). The average values of CRT showed significantly negative correlations with the reaction time in sustained attention and visual searching (P=0.04 and P<0.01, respectively). Conclusions. Our results suggest that age at onset and glycemic control had significant impacts on different cognitive domains in T1D. The CRT had a significant correlation with sustained attention, which could be a surrogate markers of brain structural changes in T1D.